2006
DOI: 10.1158/1078-0432.ccr-05-2858
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Promoter Methylation Suggests Epigenetic Progression in Squamous Cell Carcinoma of the Esophagus

Abstract: Purpose: Squamous esophageal cancer is common in non-Western countries and has a welldefined progression of preinvasive dysplasia leading to invasive squamous cell carcinoma. We examined the changes in promoter region methylation occurring during neoplastic progression. Experimental Design: The frequency of epigenetic changes in the promoter region of 14 genes epigenetically silenced in other cancers was determined and examined the most frequent changes in dysplastic lesions using methylation-specific PCR. Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
121
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 34 publications
4
121
1
1
Order By: Relevance
“…Mutations of p53 or p53 oncoprotein are relatively late events in carcinogenesis (42,43), so, despite their biological plausibility as cancer predictors, they are insufficient for risk assessments for SCC in the UADT. Because aberrant DNA methylation usually precedes neoplastic transformation, qualitative studies have suggested that the presence of methylated genes may increase in a sequence from normal mucosa to precursor lesions to SCC (44)(45)(46). Our study further found that this phenomenon is quantitative for individual gene markers.…”
Section: Discussionsupporting
confidence: 73%
“…Mutations of p53 or p53 oncoprotein are relatively late events in carcinogenesis (42,43), so, despite their biological plausibility as cancer predictors, they are insufficient for risk assessments for SCC in the UADT. Because aberrant DNA methylation usually precedes neoplastic transformation, qualitative studies have suggested that the presence of methylated genes may increase in a sequence from normal mucosa to precursor lesions to SCC (44)(45)(46). Our study further found that this phenomenon is quantitative for individual gene markers.…”
Section: Discussionsupporting
confidence: 73%
“…As disruption of processes involved in programmed cell death is a common feature of human cancers, it is significant that inactivation of DAPK by promoter methylation has been described in esophageal cancer. [20][21][22] Retinoids regulate the growth, differentiation and apoptosis of premalignant and malignant cells during carcinogenesis. RAR-β, which acts as retinoic acid-dependent transcriptional activators, predominantly mediated the effects of retinoids.…”
Section: Discussionmentioning
confidence: 99%
“…37,48,49 In our analysis of NMIBC it remains unclear whether the increase in frequency and/or mean levels of methylation in the more aggressive tumors represents a more rapid accumulation of epigenetic changes during tumor progression, or reflects distinct epigenetic pathways of tumor development and outgrowth. 50,51 Our findings may therefore reflect either of the described scenarios in the more aggressive (high-grade) tumors and suggests that these tumors are either consequent to progression from low-intermediategrade tumors, or are the progeny of aberrations in distinct epigenetic pathways within these NMIBC subtypes. Moreover, the identification of different patterns of methylation between tumors represents an important area for future investigation.…”
Section: Discussionmentioning
confidence: 73%